Industrial fluctuations - Pigou, A. C. (New York : A. M. Kelley, 1967)
This book deals with those industrial fluctuations extending over short spans of years which are sometimes called cyclical.
Part of illustrative matter in pocket.
Reprint of the 1927 ed.
Bibliographical footnotes.
oo 24/01/2019
Loans
Keywords: Business cycles; Depressions; Economic history